Membrane Insertion of New AMPA Receptors and LTP Induced by Glycine is Prevented by Blocking NR2A-Containing NMDA Receptors in the Rat Visual Cortex In Vitro - Li, Yan-Hai; Wang, Jue (Current Neurovascular Research, 2013)
N-methyl-D-aspartate receptors (NMDA-Rs) activation has been implicated in various forms of synaptic plasticity depending on the receptor subtypes involved. However, the contribution of NR2A and NR2B subunits in glycine-induced long-term potentiation (LTP) of miniature excitatory postsynaptic currents (mEPSCs) in layer II/III pyramidal neurons of the rat visual cortex remains unclear. The present study used whole-cell patch-clamp recordings in vitro to investigate the role of NR2A-containing and NR2B-containing NMDA-Rs in glycine-induced LTP in visual cortical slices from 13-15 day old rats. We found that glycine-induced LTP of mEPSCs was readily induced in layer II/III pyramidal neurons of the rat visual cortex with glycine. D-APV, a selective NMDA-R antagonist, blocked the glycineinduced LTP. Moreover, the selective NR2B-containing NMDA-R antagonists (Ro 25-6981) displayed no influence on the glycine-induced LTP. However, Zn2+, a voltage-independent NR2A-containing NMDA-R antagonist, prevented glycine-induced LTP. These results suggest that the glycine-induced LTP in layer II/III pyramidal neurons of the rat visual cortex is NMDA-R-dependent and requires NR2A-containing NMDA-Rs, not NR2B-containing NMDA-Rs.
Keywords: Visual cortex